The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0102-86502014000400007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of tissue reactivity to n-butyl-2-cyanoacrylate and nylon monofilament thread on pericranium-cutaneous flaps in rats

Abstract: PURPOSE:To study the repair of pericranium-cutaneous flaps fixed with suture anchored in a skull bone tunnel or N-butyl-2-cyanoacrylate adhesive in Wistar rats with emphasis on the cellular inflammatory response and the production of types I and III collagen. METHODS:The operated region in the cephalic region of Wistar rats was removed minutes before euthanasia, fixed in formalin, and subjected to histological preparation. Slides were stained with hematoxylin-eosin and Picrosirius. Standardized counts of polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated the efficacy of using sutures with adhesive compounds in surgery. These have the advantage of not reducing tissue perfusion caused by conventional suture and demonstrate inflammatory reactions similar to conventional or even minor suture materials in the final stages of inflammation [4,16,17]. In a comparative study between cyanoacrylate and nylon suture, cyanoacrylate has been shown to promote greater recruitment of polymorphonuclear leukocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the efficacy of using sutures with adhesive compounds in surgery. These have the advantage of not reducing tissue perfusion caused by conventional suture and demonstrate inflammatory reactions similar to conventional or even minor suture materials in the final stages of inflammation [4,16,17]. In a comparative study between cyanoacrylate and nylon suture, cyanoacrylate has been shown to promote greater recruitment of polymorphonuclear leukocytes [18].…”
Section: Discussionmentioning
confidence: 99%